A Needs Analysis for Embedding Sustainable Finance Competences into Vocational Business Education in the Baltic Region - Siirilä, Jani; Surikova, Svetlana; Margeviča-Grinberga, Ieva; Pigozne, Tamara (Journal of Education Culture and Society, 2022)
Aim. The aim of this article was to analyse relevant literature as well as financial services sector professionals’ expectations on future sustainability competence needs among vocational business graduates as part of an ideation process to design an open online course within the project “Sustainability in Finance – SuFi” (2020-2022).Methods. The online mixed-method survey was elaborated using Google Forms and Webropol and distributed via email among finance services industry professionals in Finland, Latvia, Estonia, and Aland Islands. In total, 221 responses were obtained. The qualitative and quantitative data analysis was performed using NVivo and SPSS.Results. Qualitative data analysis revealed that the conceptual knowledge of business graduates was the most frequently mentioned category, followed by procedural knowledge. Among the key competencies in sustainability, the most necessary was intra-personal competence, followed by inter-personal competence. Quantitative data analysis revealed that the top three sustainable finance competencies in demand within respondents’ organisations were: to understand relevant driving sustainable forces, to think and operate with a long-term perspective, and to communicate sustainable financial information in a meaningful way.Conclusion. In the Baltic Region’s finance sector, there is a need for a more holistic view for understanding the market as part of society as a whole and also the meaning of understanding long-term horizons. The competencies that financial services sector professionals found important for vocational business graduates in future work were used as an input for elaborating vocational business education study courses.